GREEN BUILDING CERTIFICATE SYSTEMS AS A GREENWASHING STRATEGY IN ARCHITECTURE - Kurnaz, Ahmet (Bartın Üniversitesi, 2021)
As a result of the depletion of natural resources, the destruction of green, the damage of the ecosystem, and having less habitable areas each passing day, the concept of sustainability has become an important parameter at every stage in the architecture field, from decisions related to planning and design to practice of those. All these reasons have led the way to establish green building standards and green building certification systems to reduce the negative implications of buildings on the natural environment through sustainable design. Today, green building evaluation systems have some practical problems. Recently, the increase in the tendency towards making green buildings with the purpose of advertising through the effective use of social media channels and the transformation of tendency into green building sector itself and into greenwashing strategies is the most important discussion point of the study. In the study, the concepts of sustainability, green building and green building certification systems were examined in detail, green building projects and certification systems that claim sustainability were discussed, and a theoretical perspective on green building certification systems as a greenwashing strategy in the field of architecture was introduced by referring to the evolution of environmental activist movements. Within the scope of this study, it was aimed to measure the consistency of the criteria of the green building evaluation systems that evaluate the green status of buildings on certain criteria such as LEED and BREEAM, which are becoming widespread on a global scale, by examining these systems in detail.

Doğal kaynakların tükenmesi, doğadaki yeşil alanların tahribatı, ekosisteme verilen zarar ve buna bağlı olarak yaşanılabilir alanların her geçen gün daralması sonucunda sürdürülebilirlik kavramı, tüm alanlarda olduğu gibi mimarlık disiplininde de planlama ve tasarım kararlarından uygulamaya kadar her aşamada önemli bir parametre haline gelmiştir. Bu gerçekler, binaların sürdürülebilir tasarım yoluyla doğal çevre üzerindeki olumsuz etkisini azaltmaya yönelik yeşil bina standartlarının ve yeşil bina sertifika sistemlerinin oluşturulmasına yol açmıştır. Günümüzde yeşil bina değerlendirme sistemlerinin uygulamaya yönelik bir takım sorunları mevcuttur. Özellikle son zamanlarda sosyal medya kanallarının da etkin kullanımı ile reklam amacı güdülerek yeşil binaya eğilimlerin artması ve bu konunun bütün bileşenleriyle birlikte yeşil bina sektörüne ve yeşil aklama stratejilerine dönüşüyor olması, çalışmanın en önemli tartışma konusudur. Çalışmada çevresel aktivizm hareketlerinin gelişimine değinilerek, sürdürülebilirlik, yeşil bina ve yeşil bina sertifika sistemleri kavramları etraflı bir biçimde irdelenmiş, sürdürülebilirlik iddiası taşıyan yeşil bina projeleri ve sertifika sistemleri tartışılarak, mimarlıkta yeşil aklama stratejisi olarak yeşil bina sertifika sistemleri konusuna kuramsal bir bakış açısı ortaya konmuştur. Çalışma kapsamında binaların yeşil olma niteliklerini belirli ölçütlere dayandırarak yapan bu sistemleri daha detaylı inceleyerek dünyada kullanımı giderek yaygınlaşan özellikle LEED ve BREEAM gibi yeşil bina değerlendirme sisteminin ölçütlerinin tutarlılığını ölçmek amaçlanmıştır.
MİMARLIKTA YEŞİL AKLAMA STRATEJİSİ OLARAK YEŞİL BİNA SERTİFİKA SİSTEMLERİ
Keywords: Architecture; Mimarlık